1996
DOI: 10.1007/bf00025407
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentrations in surficial sediments and benthic macroinvertebrates from Anzali wetland, Iran

Abstract: Lead, Copper, Zinc and Manganese were measured in surficial sediments, chironomid larvae, tubificid worms and two species of bivalve molluscs (Mytilaster lineatus and Corbicula fiuminalis) from the Anzali wetland, Iran .No distinct relationship was observed between heavy metal levels and percentage fine fraction in sediments . The pattern of Mn accumulation was parallel to trends of organic matter variation . There were highly significant differences between sampling sites in contents of heavy metals but no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 12 publications
2
42
0
4
Order By: Relevance
“…Some researchers found that filter-feeder species, as Mollusks, accumulate more Mn, Cu, Zn and Pb than Chironomidae species, (not analyzed in Chironomus species) 18 and some metals, appeared to be accumulated in the upper trophic levels as fishes, reptiles, birds, mammals and other organisms. 32,35 Although predator species can accumulate high concentrations of metals, our results point that, depending on the sediments contamination, the collector organisms as Chironomus larvae, because of their close association with the sediments (benthic organisms) and functional feeding group, accumulate higher concentrations of metals than other groups of aquatic insects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some researchers found that filter-feeder species, as Mollusks, accumulate more Mn, Cu, Zn and Pb than Chironomidae species, (not analyzed in Chironomus species) 18 and some metals, appeared to be accumulated in the upper trophic levels as fishes, reptiles, birds, mammals and other organisms. 32,35 Although predator species can accumulate high concentrations of metals, our results point that, depending on the sediments contamination, the collector organisms as Chironomus larvae, because of their close association with the sediments (benthic organisms) and functional feeding group, accumulate higher concentrations of metals than other groups of aquatic insects.…”
Section: Discussionmentioning
confidence: 99%
“…Then, they were identified and frozen at -20 ºC in order to perform the metal analyses. 18 Due to the importance of the amount of organic matter of the sediment in the metal absorption in the aquatic system, 23 three sediment sub-samples were collected from the streams for organic matter determination.…”
Section: Sampling and Storagementioning
confidence: 99%
See 2 more Smart Citations
“…Pourang (1996) found the species in the Anzali wetland (connected with the Caspian Sea) in Northern Iran. Ahmadi et al (2012) found T. tubifex in the Zarrineh River in the West Azarbaijan Province.…”
Section: Stylaria Lacustris (Linnaeus 1767)mentioning
confidence: 98%